Age, not sex, predicts needle fear and life interference - Caltabiano,A; Burke,T; Nesi,J; Di,Simplicio M; Van,Zalk N (Psychiatry Research Communications, 2025)
Fear of needles is common and can impair health-related behavior, yet remains underexamined in adult populations. This study assessed symptom severity and life interference associated with needle fear in a UK sample (N = 396). Findings showed 77 % of participants reported life interference due to needle fear despite almost no formal diagnosis. Younger adults had higher severity, with no significant sex differences. These results suggest a need for broad, low-barrier interventions to reduce needle fear and improve public health outcomes like vaccine uptake.